2010
DOI: 10.1016/j.energy.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Wind/hydrogen hybrid systems: Opportunity for Ireland’s wind resource to provide consistent sustainable energy supply

Abstract: Ireland with its resource of wind has the potential to use this natural resource and sustain the country's power needs for the future. However, one of the biggest drawbacks to renewable energy generation, particularly wind generated electricity is that it is an intermittent and a variable source of power. Even at the "best" sites wind varies dramatically from hour to hour and minute to minute. This leads to two main problems: 1) When the wind drops below a lower limit or goes above a higher limit the turbine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…The Proton Exchange Membrane (PEM) fuel cell is a low temperature electrochemical device that offers a promising, possibly green, alternative to traditional power sources, and other fuel cell types, in many applications, without air polluting issues [1][2][3]. PEM fuel cells use a solid polymer in the form of a solid phase proton conducting membrane as an electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The Proton Exchange Membrane (PEM) fuel cell is a low temperature electrochemical device that offers a promising, possibly green, alternative to traditional power sources, and other fuel cell types, in many applications, without air polluting issues [1][2][3]. PEM fuel cells use a solid polymer in the form of a solid phase proton conducting membrane as an electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The resource is widely available throughout the country with the greatest potential along the western and north-western Atlantic coastlines. To address the issue of intermittency of wind energy, and in particular over-generation of electricity during times of low demand, Carton and Olabi [5] investigated the possibility of hydrogen production and storage in conjunction with wind power in Ireland. In this wind/hydrogen system the excess power produced when demand is low is used in an electrolyser to produce hydrogen.…”
Section: Renewable Energy Resources In Irelandmentioning
confidence: 99%
“…Connolly et al [4] reported the maximum realisable penetration of wind energy into the Irish energy network is 30% from both an economic and a technical viewpoint. Carton and Olabi [5] reported on the performance of a single wind turbine installed in 2005 on-site at a third-level education institution on the east coast, described as the first urban turbine in Ireland. The turbine has a maximum output of 850KW and provides approximately one third of the on-campus electrical energy demand, saving €125,000 annually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such systems are able to provide fast startups and rampings, thus allowing the power system to offset the impact of renewable energy generation (Brown and Lopes, 2008;Zeng et al, 2006;Abbey and Joós, 2007;Li and Joós, 2007;Carton and Olabi, 2010). The integration of storage in weak networks with an intermittent energy source improves power quality and reduces the cost of electricity significantly .…”
Section: Introductionmentioning
confidence: 99%